2009
DOI: 10.1073/pnas.0812729106
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin 40 is required for microRNA activity in Arabidopsis

Abstract: Loss-of-function mutations of SQUINT (SQN)-which encodes theArabidopsis orthologue of cyclophilin 40 (CyP40)-cause the precocious expression of adult vegetative traits, an increase in carpel number, and produce abnormal spacing of flowers in the inflorescence. Here we show that the vegetative phenotype of sqn is attributable to the elevated expression of miR156-regulated members of the SPL family of transcription factors and provide evidence that this defect is a consequence of a reduction in the activity of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
140
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(145 citation statements)
references
References 39 publications
4
140
0
1
Order By: Relevance
“…Arabidopsis has a single AGO1 gene, rice has four paralogs (Wu et al, 2009). AGO1 preferentially binds miRNAs and small RNAs with a 5′ uridine (Bohmert et al, 1998;Vaucheret et al, 2004;Mi et al, 2008;Wu et al, 2009;Jeong et al, 2013;Rogers and Chen, 2013).…”
Section: Ago1mentioning
confidence: 99%
See 2 more Smart Citations
“…Arabidopsis has a single AGO1 gene, rice has four paralogs (Wu et al, 2009). AGO1 preferentially binds miRNAs and small RNAs with a 5′ uridine (Bohmert et al, 1998;Vaucheret et al, 2004;Mi et al, 2008;Wu et al, 2009;Jeong et al, 2013;Rogers and Chen, 2013).…”
Section: Ago1mentioning
confidence: 99%
“…Arabidopsis has a single AGO1 gene, rice has four paralogs (Wu et al, 2009). AGO1 preferentially binds miRNAs and small RNAs with a 5′ uridine (Bohmert et al, 1998;Vaucheret et al, 2004;Mi et al, 2008;Wu et al, 2009;Jeong et al, 2013;Rogers and Chen, 2013). Analysis of miRNAs loaded onto AGO1 paralogs in rice suggested that a subset of miRNAs is specifically incorporated into or excluded from one of these paralogs suggesting they have both redundant and specialized roles in rice (Wu et al, 2009).…”
Section: Ago1mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the emu mutation enhanced the slightly altered phyllotaxy of ago1-27 inflorescences, wherein the internode length is more random than that in wild-type plants, resulting in multiple fruits emanating from the same node ( Fig. 4O,P ;Morel et al 2002;Smith et al 2009). Taken together, these data suggest that EMU may be involved in assuring proper miRNA action.…”
Section: Genetic Interactions Between Emu and Mirna Mutantsmentioning
confidence: 99%
“…We scored affected seedlings rather than the frequency of lesions because lesions often fused with each other, confounding frequency measures. For the ago1-25, ago1-27, and ago1-46 mutant seedlings (Morel et al, 2002;Smith et al, 2009), the frequency of affected seedlings increased significantly in full-spectrum light compared with the wild type (Fig. 1).…”
mentioning
confidence: 93%